Silicon Composite Materials
Porous silicon composite particles with a high silicon-to-carbon ratio and carbon nanotube/graphene networks, sealed with a carbon coating, address the volume expansion and stability issues of silicon anodes in lithium-based batteries, enhancing cycle life and efficiency.
Patent Information
- Application Number
- JP2024547240
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-02-09
- Filing Date
- 2023-02-03
- Publication Date
- 2025-03-18
AI Technical Summary
Current silicon anode materials for lithium-based batteries face challenges such as large volume changes during lithiation, resulting in cracking, unstable solid electrolyte interfaces, and low initial Coulomb efficiency, which limit cycle life and capacity utilization.
The development of porous silicon composite particles with a high silicon-to-carbon ratio, where silicon nanoparticles are embedded in a carbon network, including carbon nanotubes and graphene, and sealed with a thin carbon coating to manage volume expansion and protect against electrolyte interaction.
This approach enhances the porosity and structural integrity of the anode, allowing for up to 300% swelling during lithiation, while maintaining high conductivity and reducing surface reactions, thereby improving cycle life and first cycle efficiency.
Smart Images

Figure 2025507348000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims priority from Australian Provisional Patent Application No. 2022 / 900263, filed February 9, 2022, the contents of which are to be understood as incorporated herein.
[0002] The present invention relates to silicon composite materials for use as anode materials in lithium-based batteries.
[0003] The present invention will be described with reference to preferred embodiments thereof, but those skilled in the art will recognize that the spirit and scope of the invention can be embodied in many other forms. [Background technology]
[0004] Any discussion of prior art throughout this specification should in no way be taken as an admission that such prior art is widely known or forms part of the common general knowledge in the art.
[0005] As society develops, the increasing demand for energy becomes more prominent in areas such as electronics, renewable energy generation systems, and electric vehicles. One means of addressing this ever-increasing demand is through improved battery technology.
[0006] Lithium-ion batteries (LIBs) are considered candidates for the increasing demand of portable electronic devices and electric and hybrid vehicles due to their high energy density and stable cycle life.
[0007] A typical LIB consists of a lithium metal cathode and an anode separated by a liquid electrolyte that transfers lithium between the two electrodes. The battery provides power by releasing lithium from the anode to the cathode through the electrolyte. To date, most lithium-ion batteries use anodes made of graphite, layers of carbon sheets arranged in a hexagonal pattern. The wide spaces between these layers provide the perfect place to store the lithium atoms that move in and out of the anode as the battery charges and discharges. The maximum amount of lithium that can be stored in the anode determines the capacity of the battery and limits the distance a car can be driven before needing to be recharged. Conventional lithium-ion batteries with graphite anodes have a capacity of about 370 mAh / g, enough to power a laptop but not enough for long journeys.
[0008] Among various anode materials, silicon has the highest theoretical specific capacity (about 4200 mAh g−1), which is 10 times higher than conventional carbon anodes. -1 ) and sufficient potential for lithium insertion and extraction (<0.5V vs. Li / Li + ) and has attracted considerable attention.
[0009] Unfortunately, the practical application of Si anodes is currently hindered by several challenges. The main drawbacks are the large volume change (~300%) upon full lithiation and the resulting expansion / contraction stresses during lithiation / delithiation, which can induce serious cracking of Si. This leads to the formation of an unstable solid electrolyte interface (SEI) on the Si surface, causing lithium trapping in the active Si material, resulting in irreversible fast capacity loss and low initial coulombic efficiency (CE). This creates problems with cycle life and also electrode swelling, which should be kept below ~20% in commercial cells.
[0010] Furthermore, the slow lithium diffusion kinetics in Si (10 -14 ~10 -13 cm 2 s -1) and the low intrinsic electrical conductivity of Si (10 -5 ~10 -3 Scm -1 ) also significantly affects the rate capability and total capacity utilization of the Si electrode.
[0011] To improve cycle life, the use of nano-sized silicon has been shown to provide acceptable cycle life because it can accommodate the strain on expansion. However, this results in a high surface area, leading to significant reaction with the electrolyte and low first cycle efficiency. Nano-sized silicon can also be somewhat expensive.
[0012] Silicon nanostructured materials, including nanotubes, nanowires, nanorods, nanosheets, porous and hollow or encapsulated Si particles with protective coatings, have been explored to achieve improved structural and electrical performance.
[0013] Meanwhile, the preparation methods for these nanostructures (e.g., gas-liquid-solid method, magnetron sputtering, and chemical vapor deposition) are generally complicated techniques and multiple steps. Graphite and porous carbon are potential anode materials with relatively small volume changes during the lithiation-delithiation process (e.g., about 10.6% for graphite), and have excellent cycle stability and electronic conductivity. Compared with silicon, carbon materials have similar properties and can be closely combined with each other, making them a natural choice as a matrix material (i.e., dispersion carrier) for dispersing silicon particles. Therefore, silicon-carbon composite anodes have been extensively studied for their higher capacity, better electronic conductivity, and cycle stability. However, there is a need to overcome the problems of silicon-carbon anode materials, such as low first discharge efficiency, poor conductivity, and poor cycling performance.
[0014] Previous work [Li, X., et al. “Mesoporous Silicon Sponge as an Anti-Pulverisation Structure for High-Performance Lithium-Ion Battery Anodes”, Nature Communications, 5:4105, 2014] prevented this volume expansion by breaking down silicon anodes into many small nanoparticles embedded in another material to give them space to swell. However, this solution only creates more problems. The small Si nanoparticles that solve the expansion problem are vulnerable to irreversible reactions with the liquid electrolyte that permeates the anode (known as the solid electrolyte interface). These reactions hinder the silicon's ability to take up lithium ions and reduce the overall life of the battery. In addition, the small particles have poor conductivity, reducing the battery's ability to provide enough current to power a car or other device. So far, no anode design has been able to both limit the volume expansion and prevent undesirable side effects such as electrolyte interactions and low conductivity.
[0015] Recently, a collaboration between the University of Waterloo and General Motors developed a new method to protect tiny silicon particles from the electrolyte while preserving their electrical conductivity. The method forms a structural scaffold around silicon nanoparticles that allows lithium ions to intercalate but keeps the electrolyte out. The design combines three different materials: Si nanoparticles, graphite sheets that contain sulfur instead of some carbon atoms (sulfur-doped graphene), and an organic polymer known as polyacrylonitrile (PAN). After mixing all the components together, the silicon nanoparticles tend to covalently bond with the sulfur sites in the graphite. This strong interaction naturally forms a network of silicon particles attached to the intermittent sulfur positions between the graphite layers.
[0016] Slowly heating the mixture to about 450°C builds a structural framework of PAN around and between the graphite layers. The ability of PAN to thread throughout the graphene-Si structure shields the Si nanoparticles from the electrolyte while also providing a dense network of molecules along which electrons can move. Thus, the anode design solves both the electrolyte and conductivity problems seen in previous anode designs. At the same time, the Si nanoparticles are well attached to the sulfur-doped graphene sheets and have enough room to expand between the graphite layers during lithium intercalation.
[0017] It is an object of the present invention to overcome or ameliorate at least one of the disadvantages of the prior art, or to provide a useful alternative.
[0018] The present invention generally relates to porous silicon composite particles that address one or more of the many problems associated with silicon.Without being bound by any one theory, the inventors believe that when the Si to carbon ratio is high (e.g., at least 75% silicon), the porous silicon composite particles may be held together by a small amount of carbon.
[0019] It is an object of particularly preferred forms of the present invention to provide composite particles and methods of production that provide enhanced porosity with high silicon content relative to carbon, while also preferably being capable of being sealed with a coating of suitable thickness.
[0020] Although the invention will be described with reference to specific examples, those skilled in the art will appreciate that the invention can be embodied in many other forms.
[0021] definition In describing and defining the present invention, the following terminology will be used in accordance with the definitions set out below. It is also to be understood that the terminology used herein is for the purpose of describing particular embodiments of the invention only, and is not intended to be limiting.
[0022] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0023] Unless the context clearly requires otherwise, throughout the description and claims, the words "comprise", "comprising", and the like, are to be interpreted in their inclusive sense, i.e., "including but not limited to," rather than in their exclusive or exhaustive sense.
[0024] As used herein, the phrase "consisting of" excludes any element, step, or ingredient not specified in the claim. When the phrase "consists of" (or variations thereof) appears in a section of the body of a claim rather than immediately following the preamble, it limits only the elements recited in that section and does not exclude other elements from the claim as a whole. As used herein, the phrase "consisting essentially of" limits the claim to the elements or methods specified and to those that do not materially affect the basic and novel feature(s) of the claimed subject matter.
[0025] With respect to the terms "comprising," "consisting of," and "consisting essentially of," where one of these three terms is used herein, the presently disclosed and claimed subject matter may also include the use of either of the other two terms. Thus, in some embodiments not expressly stated otherwise, any instance of "comprising" may be replaced with "consisting of" or alternatively "consisting essentially of."
[0026] Except in the operating examples or where otherwise indicated, all numbers expressing amounts of ingredients or reaction conditions used herein should be understood to be modified in all cases by the term "about", taking into account normal tolerances in the art. The examples are not intended to limit the scope of the invention. Hereinafter, or where otherwise indicated, "%" means "% by weight", "ratio" means "ratio by weight", and "parts" means "parts by weight".
[0027] As used herein, unless otherwise indicated, the term "substantially" is intended to mean including more than 50%, where relevant.
[0028] The recitation of numerical ranges with endpoints includes all numbers subsumed within that range (e.g., 1 to 5 includes 1, 1.5, 2, 2.75, 3, 3.80, 4, 5, etc.).
[0029] The terms "preferred" and "preferably" refer to embodiments of the invention that may provide certain benefits, under certain circumstances. However, other embodiments may also be preferred, under the same or other circumstances. Furthermore, the recitation of one or more preferred embodiments does not imply that other embodiments are not useful, and is not intended to exclude other embodiments from the scope of the invention.
[0030] It should also be noted that as used in this specification and the appended claims, the singular forms "a," "an," and "the" include plural references unless the context clearly dictates otherwise.
[0031] As used herein, the term "lithium ion battery" refers to any battery that uses Li ions to shuttle charge between an anode and a cathode, such as conventional lithium ion batteries, lithium metal batteries (such as lithium zinc batteries), and lithium sulfur batteries. Those skilled in the art will appreciate that while the Li ions transfer charge, dopants or additives may be present in the anode and / or cathode of a lithium ion battery. Examples of dopants or additives include zinc or sulfur.
[0032] Those skilled in the art will appreciate that the embodiments described herein are merely exemplary, and that the electrical features of the present application may be configured in various alternative arrangements without departing from the spirit or scope of the present invention.
[0033] Although exemplary embodiments of the disclosed technology are described in detail herein, it should be understood that other embodiments are contemplated. Thus, the disclosed technology is not intended to be limited in scope to the details of construction and the arrangement of components set forth in the following description or illustrated in the drawings. The disclosed technology is capable of other embodiments and of being practiced or carried out in various ways. Summary of the Invention
[0034] Applicants have surprisingly discovered that certain composite properties can be achieved using silicon nanoparticles, various forms of carbon, and carbon coatings that render the resulting coated Si:C nanoparticles amenable for use in lithium-based batteries, such as lithium-ion batteries.
[0035] Moreover, applicants have surprisingly discovered methods for producing the composites that generally comprise low cost processes.
[0036] Preferred embodiments of the present invention incorporate low cost silicon and amounts of various allotropes of carbon that are optimized to achieve an advantageous combination of cost and performance in the resulting LIB.
[0037] According to a first aspect of the present invention, there is provided a silicon composite comprising nanoscale silicon and carbon in a weight ratio (silicon:carbon) of about 75:25 to about 99:1, and having a volume fraction of porosity of about 20 to about 70%.
[0038] In one embodiment, the weight ratio of nanoscale silicon to carbon is from about 90:10 to about 96:4.
[0039] In one embodiment, the volume fraction of porosity is from about 50% to about 60%.
[0040] In one embodiment, the porosity of the composite accommodates swelling of up to about 300% during the lithiation-delithiation process.
[0041] In one embodiment, the carbon is a fibrous form of carbon, such as carbon nanotubes (CNTs), and / or thin nanoplates, such as graphene or graphene oxide or reduced graphene oxide, or combinations thereof.
[0042] In one embodiment, the composite further comprises carbon produced by pyrolysis of polymer precursors such as sugars, including glucose, sucrose, fructose, and the like.
[0043] In one embodiment, the composite is encapsulated with a carbon coating of appropriate thickness.
[0044] In one embodiment, the coating reduces the available (effective) surface area of the Si:C particles by about 50 to about 80%.
[0045] In one embodiment, the coating is less than about 500 nm thick.
[0046] In one embodiment, the composite is for use in a lithium-based battery, particularly a lithium-ion battery.
[0047] In one embodiment, the composite is for use as an anode in a lithium-based battery, particularly a lithium-ion battery.
[0048] In one embodiment, the composite is for use as a cathode in a lithium-based battery, particularly a lithium-ion battery.
[0049] According to a second aspect of the present invention, there is provided an anode for a lithium-ion battery comprising a silicon composite according to the first aspect of the present invention.
[0050] According to a third aspect of the present invention, there is provided a cathode for a lithium-ion battery comprising a silicon composite according to the first aspect of the present invention.
[0051] According to a fourth aspect of the present invention, there is provided a half-cell for a lithium-ion battery comprising an anode according to the second aspect of the present invention, a binder, and a conductive additive, in a weight ratio of composite to binder to conductive additive of about 8:1:1, 9:0.5:0.5, 95:0.2:0.3, or 97:1:2.
[0052] According to a fifth aspect of the present invention, there is provided a half-cell for a lithium-ion battery comprising a cathode according to the third aspect of the present invention, a binder, and a conductive additive, in a weight ratio of composite to binder to conductive additive of about 8:1:1, 9:0.5:0.5, 95:0.2:0.3, or 97:1:2.
[0053] In certain embodiments, the conductive additive is graphite. In some embodiments, the graphite can be natural graphite, synthetic graphite, amorphous graphite, calcined petroleum coke, crystalline flake graphite, natural flake graphite, surface enhanced flake graphite, expandable graphite, refined flake graphite, refined crystalline flake graphite, refined petroleum coke, refined synthetic graphite, refined flake graphite, synthetic graphite, primary artificial graphite, secondary artificial graphite, spherical natural graphite, flake graphite, and combinations thereof. In some embodiments, the conductive additive is in the form of a composite final anode product. In some embodiments, the conductive additive is a graphite anode.
[0054] In some embodiments, the conductive additive is conductive carbon. In some embodiments, the conductive carbon is selected from the group consisting of carbon black (such as super P® or Imerys C45), activated carbon, carbon nanotubes and their derivatives; graphene and their derivatives; and combinations thereof.
[0055] In some embodiments, the binder is selected from the group consisting of at least one of a linear polymer, a conductive polymer, a self-healing polymer, a rubber polymer, and combinations thereof.
[0056] In one embodiment, the one or more linear polymers are selected from hydroxyl groups, amine groups, or carboxyl groups of a linear polymer.
[0057] In one embodiment, the one or more conductive polymers are selected from imino or sulfonic acid groups of conductive polymers.
[0058] In one embodiment, the one or more self-healing polymers are selected from urea groups of self-healing polymers.
[0059] In one embodiment, the one or more linear polymers are selected from the group consisting of sodium carboxymethylcellulose (CMC), polyacrylic acid (PAA), lithium polyacrylate (LiPAA), polyvinyl alcohol (PVA), sodium alginate (SA), and chitosan (CS).
[0060] In one embodiment, the one or more conductive polymers are selected from the group consisting of polyaniline (PANI), poly[9,9-bis(3-propanoate)fluorine]sodium (PFCOONa), poly(1-pyrenemethylmethacrylate-co-methacrylic acid) (PPyMAA), polypyrrole (PPY), and 3,4-ethylenedioxythiophene / polystyrene-4-sulfonate (PEDOT:PSS).
[0061] In one embodiment, the one or more self-healing polymers are selected from the group consisting of urea-pyrimidinone (UPy), urea-oligo-amidoamine (UOAA), dopamine methacrylamide (DMA), and dopamine (DA). In one embodiment, the one or more self-healing polymers are urea-oligo-amidoamine (UOAA).
[0062] In one embodiment, the one or more rubber polymers are selected from the group consisting of styrene butadiene rubber (SBR), neoprene, nitrile rubber, butyl silicone rubber, and polysulfide rubber.
[0063] In one embodiment, the binder is carboxymethyl cellulose (CMC) / styrene-butadiene rubber (SBR) and the conductive additive is Imerys C45 carbon black.
[0064] In one embodiment, the counter electrode is lithium metal.
[0065] According to a sixth aspect of the present invention, there is provided a lithium-ion battery comprising an anode according to the second aspect of the present invention, a cathode, an electrolyte, and a separator.
[0066] According to a seventh aspect of the present invention, there is provided a lithium-ion battery comprising a cathode according to the seventh aspect of the present invention, an anode, an electrolyte, and a separator.
[0067] In one embodiment, the electrolyte is selected from metals or transition metals including sulfates, sulfites (including bisulfites), phosphates, hexafluorophosphates, carbonates, bicarbonates, hydroxides, permanganates, chromates, dichromates, oxalates, formates, acetates, benzoates, halides, chlorites, perchlorates, and hypochlorites (e.g., perfluorates, hypobromites, etc.), acids, and mixtures thereof. In a particularly preferred embodiment, the electrolyte is ammonium sulfate, lithium hexafluorophosphate, iron sulfate, or mixtures thereof. In another embodiment, the electrolyte is sulfuric acid or nitric acid. Preferably, the electrolyte is iron sulfate, lithium hexafluorophosphate, or ammonium sulfate.
[0068] In further embodiments, the electrolyte is selected from sulfides, phosphides, phenolates, superoxides, peroxides, oxides, silicates, sulfones, thiocyanates, thiosulfates, selenates, triiodides, azides, cyanides, cyanates, borates, fulminates, arsenates, vanadates, antimonates, and the like.
[0069] In one embodiment, the cathode includes lead, lead alloys, and combinations thereof, hi one embodiment, the cathode includes platinum and graphite electrodes, various grades of stainless steel, iron alloys, other transition metal alloys, and the like.
[0070] In one embodiment, the process further includes the use of a separator, which is typically a permeable membrane disposed between the cathode or anode, or both. Preferably, the permeable membrane is a neutral charge permeable membrane, an anion exchange membrane, or a cation exchange membrane. More preferably, the permeable membrane is selected from asbestos cloth, cellulose, glass cloth, filter cloth, glass cloth impregnated with silica gel, porous sintered stainless steel, vinyl chloride acrylonitrile, polysulfone, polyethersulfone (PES), polycarbonate, polytetrafluoroethylene, polyethylene terephthalate (PET), polyolefin, polyethylene, polypropylene, porous poly(methyl methacrylate)-grafted and / or siloxane-grafted polyethylene, polyvinylidene fluoride (PVDF), and combinations thereof. Alternatively, the membrane may include sintered metal and non-metallic materials, such as ceramics.
[0071] In one embodiment, the separator has a molecular weight cut-off (MWCO) of less than about 1 million Da. Preferably, the separator has a molecular weight cut-off (MWCO) of between about 10 kDa and about 0.5 kDa. More preferably, the separator has a molecular weight cut-off (MWCO) of about 3.5 kDa. In one embodiment, the separator has a flow rate of 0.1 to 100 L / min / dm at 200 Pa. 2 Preferably, the separator has a gas permeability of 1 to 50 L / min / dm at 200 Pa. 2 More preferably, the separator has a gas permeability of 2 to 30 L / min / dm at 200 Pa. 2 It has good breathability.
[0072] According to an eighth aspect of the present invention there is provided a method for making a silicon composite comprising nanoscale silicon and carbon, comprising the steps of:
[0073] (a) preparing a dispersion of silicon nanoparticles and a selected morphology(s) of carbon;
[0074] (b) spray drying the dispersion to form essentially spherical, micrometer-sized composite particles;
[0075] (c) heat treating the composite particles to pyrolyze and / or burn off any polymer and strengthen the composite particles;
[0076] (d) coating the composite particles with carbon to form a Si:C composite;
[0077] (e) optionally adding additional elements, such as lithium, magnesium, nitrogen, and halogen gases, to the composite during either the heating step (c) or the coating step (d), or during a subsequent heat treatment step.
[0078] According to a ninth aspect of the present invention there is provided a method for making a silicon composite comprising nanoscale silicon and carbon, comprising the steps of:
[0079] (a) preparing a dispersion of silicon nanoparticles by grinding in water and maintaining a mixture of silicon and water;
[0080] (b) optionally preparing a separate dispersion of the selected form(s) of carbon in water, optionally containing one or more surfactants;
[0081] (c) adding the carbon dispersion and optional surfactant mixture (or carbon in undispersed form) to the silicon-water dispersion;
[0082] (d) dispersing the resulting mixture;
[0083] (e) spray drying the resulting dispersed Si:C mixture to form essentially spherical particles;
[0084] (f) heat treating the essentially spherical particles to pyrolyze and / or burn off any polymer and strengthen the spherical Si:C particles;
[0085] (g) coating the heat-treated spherical Si:C particles with carbon using a chemical vapor deposition process to form a carbon-coated Si:C composite;
[0086] (h) optionally adding additional elements, such as lithium, magnesium, nitrogen, and halogen gases, to the carbon-coated Si:C composite during either the mixing step (c) or the dispersing step (d) or during a subsequent heat treatment.
[0087] In one embodiment of the eighth or ninth aspect, the selected form(s) of carbon comprises carbon nanotubes (CNTs) and / or thin nanoplates, such as graphene or graphene oxide or reduced graphene oxide, and combinations thereof. In a preferred embodiment, the selected form of carbon is a carbon nanotube, preferably a single-walled carbon nanotube (SWCNT).
[0088] In one embodiment of the eighth or ninth aspect, the weight ratio of nanoscale silicon to carbon is from about 90:10 to about 96:4.
[0089] In an embodiment of the ninth aspect, the surfactant(s) is non-ionic.
[0090] In an embodiment of the eighth or ninth aspect, the carbon further comprises carbon produced by pyrolysis of polymer precursors such as sugars, including glucose, sucrose, fructose, and the like.
[0091] In one embodiment of the eighth or ninth aspect, the volume fraction of porosity in the particle before coating is from about 50% to about 60%.
[0092] In an embodiment of the eighth or ninth aspect, the composite is encapsulated with a carbon coating of suitable thickness.
[0093] In one embodiment of the eighth or ninth aspect, the coating reduces the available (effective) surface area of the Si:C particles by about 50 to about 80%.
[0094] In one embodiment of the eighth or ninth aspect, the coating has a thickness of less than about 500 nm.
[0095] According to a tenth aspect of the present invention there is provided a silicon composite comprising nanoscale silicon and carbon when produced by a process according to the eighth aspect of the present invention.
[0096] According to an eleventh aspect of the present invention there is provided a carbon coated silicon composite comprising nanoscale silicon and carbon when produced by a process according to the ninth aspect of the present invention.
[0097] According to a twelfth aspect of the present invention, there is provided an anode for a lithium-ion battery comprising a silicon composite according to the tenth aspect of the present invention or a carbon-coated silicon composite according to the eleventh aspect.
[0098] According to a thirteenth aspect of the present invention, there is provided a half-cell for a lithium-ion battery comprising an anode according to the twelfth aspect of the present invention, a binder, and a conductive additive, in a weight ratio of composite to binder to conductive additive of about 8:1:1, 9:0.5:0.5, 95:0.2:0.3, or 97:1:2.
[0099] According to a fourteenth aspect of the present invention, there is provided a lithium-ion battery comprising an anode according to the twelfth aspect of the present invention, a cathode, an electrolyte, and a separator.
[0100] According to a fifteenth aspect of the present invention there is provided a silicon composite particle comprising at least 75% silicon relative to carbon and at least 50% pores, the carbon being composed of carbon nanotubes.
[0101] According to a sixteenth aspect of the present invention there is provided a silicon composite material comprising at least 50% pores and the amount of silicon in the material is greater than 90%.
[0102] Preferred embodiments of the present invention will now be described, by way of example only, with reference to the accompanying drawings, in which: [Brief description of the drawings]
[0103] [Figure 1] Scanning electron microscope (SEM) images of uncoated particles of the composite of the invention; 8.0 kV; scale 1 μm (a) and 100 nm (b). Figure 1 shows a scanning electron microscope image of the particles. The porous carbon network (1) contains silicon nanoparticles (2) that are very well distributed, i.e., most of the nanoparticles are not in contact with each other. [Diagram 2] Scanning electron microscope (SEM) images of uncoated and coated particles of the composite material of the present invention; 8.0 kV; scale 1 μm (a) and (b) are shown. FIG. 2 shows scanning electron microscope images of the particles before and after coating. The coating encapsulates at least 90% of the surface. In a similar experiment, the coating was found to reduce the surface area from about 100 m2 / g to about 5 m2 / g, indicating that the Si nanoparticles are effectively encapsulated by the coating. [Diagram 3] Figure 1 shows the porosity (pore size distribution) of the particles from Example 1 before coating. The porosity, as measured by mercury porosimetry, was 54%. [Figure 4] FIG. 1 shows a typical coin-on-coin lithium ion battery having an anode comprising a Si:C composite produced according to Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0104] Porous particles comprising silicon and carbon are attractive as desirable anode materials because the pores can internally absorb the swelling of the silicon, thus reducing swelling in the electrode itself. A high level of porosity is desirable because it allows higher levels of silicon to be incorporated while still allowing swelling.
[0105] Carbon can play several roles in the Si:C composite of the present invention. First, it can separate the silicon particles so that they do not collide with each other when they swell. The carbon network can also add strength and elasticity to the composite particles and provide a strong network for the conduction of electrons and lithium ions. However, the weight and volumetric capacity of carbon is much smaller than that of silicon. Therefore, it is desirable to have a low amount of carbon while still allowing the carbon network to perform its various functions.
[0106] Carbon nanotubes are a good potential source of carbon because their very small diameters can provide networks with very low volume fractions of carbon. Similarly, graphene and / or graphite nanoplatelets can produce networks that are very thin and also have low volume fractions.
[0107] Typically, a sufficient amount of carbon is required in a Si:C composite, as it is understood that carbon provides porosity in the Si:C composite. The amount of carbon required typically exceeds 30% to achieve sufficient porosity. The inventors have surprisingly found that high silicon content Si:C composites can still provide sufficient porosity of more than 50%, especially when less than 30% and more preferably less than 10% carbon is used.
[0108] For commercially relevant products, it is necessary to have a high level of porosity. In some embodiments, the volume fraction of porosity (V f ) vs. V fThe silicon is about 2 to allow for internal expansion of the silicon. In another embodiment, the V f Porosity vs. V f The ratio of silicon is about 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, or about 4.0.
[0109] Preferably, the amount of carbon should be minimized while still providing a sufficiently strong conductive network.
[0110] Finally, the highly porous structure must be able to be sealed with a sufficiently thin coating so that the weight and volumetric capacity are not significantly reduced by the coating. By sealing the particles, the liquid electrolyte cannot directly access the surface of the silicon, and therefore the silicon-electrolyte reaction is minimized. However, highly porous structures would not normally be expected to be good for coating. Also, coating is highly dependent on the nucleation and growth of the coating, and therefore on the structure of the surface. For nanoscale materials, such structures can be very difficult, if not impossible, to predict in terms of the outcome for the coating process.
[0111] The inventors have found that suitable Si:C composites can increase the first cycle efficiency and / or increase the cycle life by the following steps:
[0112] (a) preparing a dispersion of silicon nanoparticles and a selected morphology(s) of carbon;
[0113] (b) spray drying the dispersion to form essentially spherical composite particles;
[0114] (c) heat treating the silicon nanoparticles to pyrolyze and / or burn off any polymer and strengthen the composite particles;
[0115] (d) coating the composite particles with carbon to form a Si:C composite;
[0116] (e) optionally adding additional elements to the composite either during the heating step (c) or the coating step (d), or during a subsequent heat treatment step. Examples include lithium, magnesium, nitrogen, and may further include halogen gases.
[0117] A preferred embodiment of the method of the present invention comprises the following steps.
[0118] (a) preparing a dispersion of silicon nanoparticles by grinding in water and maintaining a mixture of silicon and water;
[0119] (b) optionally preparing a separate dispersion of the selected form(s) of carbon in water, optionally including one or more surfactants;
[0120] (c) adding the carbon dispersion and optional surfactant mixture (or carbon in undispersed form) to the silicon-water dispersion;
[0121] (d) dispersing the resulting mixture;
[0122] (e) spray drying the resulting dispersed Si:C mixture to form essentially spherical particles;
[0123] (f) heat treating the essentially spherical particles to pyrolyze and / or burn off any polymer and strengthen the spherical Si:C particles;
[0124] (g) coating the heat-treated spherical Si:C particles with carbon using a chemical vapor deposition process to form a carbon-coated Si:C composite; and
[0125] (h) Optionally, adding additional elements to the carbon-coated Si:C composite either during the mixing step (c) or the dispersion step (d) or during the subsequent heat treatment that can increase the first cycle efficiency and / or increase the cycle life. Examples include lithium, magnesium, nitrogen, and halogen gases.
[0126] In this embodiment, costs are reduced compared to the current state of the art by (i) using ground metallurgical silicon that is ground in water instead of organic solvents, (ii) forming silicon nanoparticles, and (iii) avoiding drying of the silicon nanoparticles to maintain the separation of nanoparticle silicon (i.e., discrete nanoparticles of silicon) and maintain a high rate of porosity. If the silicon dries, the composite may collapse before pyrolysis.
[0127] In preferred embodiments, the porous Si:C composite has a high level of porosity, which allows for high levels of silicon to be incorporated while still allowing for swelling after full lithiation and expansion / contraction stresses induced during lithiation / delithiation.
[0128] Preferably, the volume fraction of porosity in the particles is greater than 30%, or greater than 40%, or greater than 50%, or about 60%. In other embodiments, the volume fraction of porosity is greater than about 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, or about 70%.
[0129] In some embodiments, the volume fraction of porosity is about twice the volume fraction of silicon, while in other embodiments, the volume fraction of porosity is about 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2.0, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, or about 3.5 times the volume fraction of silicon.
[0130] The porosity of the Si:C composite accommodates a swelling of up to about 300%. In one embodiment, the swelling is up to about 350, 340, 330, 320, 310, 300, 290, 280, 270, 260, 250, 240, 230, 220, 210, 200, 190, 180, 170, 160, 150, 140, 130, 120, 110, or about 100%.
[0131] In a preferred embodiment, the silicon to carbon ratio is maximized while achieving the preferred porosity volume fraction cited above. Silicon has a much higher gravimetric and volumetric capacity than carbon. Therefore, maximizing the silicon to carbon ratio is desirable for both gravimetric and volumetric capacity.
[0132] The silicon to carbon ratio is an important feature of the present invention. In one embodiment, the ratio can be about 75:25 to about 96:4, about 80:20 to about 96:4, about 90:10 to about 96:4, or about 92:8 to about 96:4 on a weight basis. Mixtures of various forms of carbon can provide desired performance and cost. In other embodiments, the silicon to carbon ratio is about 75:25, 76:24, 77:23, 78:22, 79:21, 80:20, 81:19, 82:18, 83:17, 84:16, 87:13, 88:12, 89:11, 90:10, 91:9, 92:8, 93:7, 94:6, 95:5, or 96:4 w / w.
[0133] In a preferred embodiment, the carbon may be provided by a fibrous form of carbon, such as carbon nanotubes (CNTs), preferably SWCNTs. Low diameter CNTs have the advantage of being able to provide a mechanically stable framework with a low volume fraction of carbon. Very thin nanoplates, such as graphene or graphene oxide or reduced graphene oxide, may also help to achieve a framework with a low volume fraction of carbon. In other embodiments, the carbon may be a mixture of carbon forms, for example CNTs interspersed with graphene platelets. In a preferred embodiment, the carbon is provided as carbon nanotubes, preferably single-walled carbon nanotubes.
[0134] In some embodiments, the carbon network may be improved by small amounts of carbon produced by pyrolysis of polymer precursors. Examples of polymer precursors are sugars, including glucose, sucrose, fructose, etc., and pitch. Such materials may improve the connectivity of the carbon network and provide elasticity and / or improved Li-ion conductivity and / or improved electronic conductivity.
[0135] The amount of carbon produced in this manner may be less than 20%, or less than 10%, or less than 5% of the weight of the uncoated composite. In other embodiments, the amount of carbon produced in this manner may be less than about 30, 29, 28, 27, 26, 25, 24, 23, 22, 21, 20, 19, 18, 17, 16, 15, 14, 13, 12, 11, 10, 9, 8, 7, 6, 5, 4, 3, 2, or less than about 1% of the weight of the uncoated composite.
[0136] In certain embodiments, the nanoscale silicon has an average particle size of about 50 nm to about 500 nm. In certain embodiments, the nanoscale silicon has an average particle size of about 50 nm to about 450 nm. In certain embodiments, the nanoscale silicon has an average particle size of about 50 nm to about 400 nm. In certain embodiments, the nanoscale silicon has an average particle size of about 50 nm to about 350 nm. In certain embodiments, the nanoscale silicon has an average particle size of about 50 nm to about 300 nm. In certain embodiments, the nanoscale silicon has an average particle size of about 50 nm to about 250 nm. In certain embodiments, the nanoscale silicon has an average particle size of about 50 nm to about 200 nm. In certain embodiments, the nanoscale silicon has an average particle size of about 50 nm to about 150 nm. In certain embodiments, the nanoscale silicon has an average particle size of about 80 nm to about 120 nm. In certain embodiments, the nanoscale silicon has an average particle size of about 100 nm.
[0137] As will be appreciated by those skilled in the art, any suitable surfactant can be used in the present invention. In certain embodiments, the co-surfactant is selected from the group consisting of non-ionic surfactants, ionic surfactants, or zwitterionic surfactants. In some embodiments, the surfactant is a polar solvent. In some embodiments, the co-surfactant comprises an alcohol group. In a preferred embodiment, the surfactant is an alcohol (-OH). In some embodiments, the co-surfactant comprises a primary alcohol. In some embodiments, the surfactant comprises a secondary alcohol.
[0138] In one embodiment, the surfactant comprises a functional group selected from the group consisting of sulfate, sulfonate, phosphate, carbonate, amine, ammonium, alcohol, ether, and combinations thereof.
[0139] In one embodiment, the anionic co-surfactant is selected from the group consisting of ammonium lauryl sulfate, sodium lauryl sulfate, sodium laureth sulfate, sodium myreth sulfate, dioctyl sodium sulfosuccinate, perfluorooctanesulfonate, perfluorobutanesulfonate, sodium lauroyl sarcosinate, perfluorononanoate, ferfluorooctanoate, sodium stearate, stearates, oleates, linoleates, linoleneates, eicosapentaenoates, docosahexaenoates, and combinations thereof; salts, solvates, dimers, isomers, chelates, or enantiomers thereof.
[0140] In one embodiment, the cationic co-surfactant is selected from the group consisting of cetrimonium bromide, cetylpyridinium chloride, benzalkonium chloride, benzethonium chloride, dimethyldioctadecylammonium chloride, phosphatidylcholine, dioctadecyldimethylammonium bromide, and combinations thereof; salts, solvates, dimers, isomers, chelates, or enantiomers thereof.
[0141] In one embodiment, the zwitterionic surfactant is selected from the group consisting of sultaines and betaines, hi one embodiment, the zwitterionic surfactant is selected from the group consisting of hydroxysultaine, (3-[(3-cholamidopropyl)dimethylammonio]-1-propanesulfonate), cocoamidopropyl betaine, cocamidopropyl hydroxysultaine, phosphatidylserine, phosphatidylethanolamine, phosphatidylcholine, sphingomyelin, lauryldimethylamine oxide, myristamine oxide, and combinations thereof.
[0142] In one embodiment, the nonionic surfactant is selected from the group consisting of narrow range ethoxylates, octaethylene glycol monododecyl ether, pentaethylene glycol monododecyl ether, nonoxynol, Triton X-100, polyethoxylated tallowamine, cocamide monoethanolamine, cocamide diethanolamine, glycerol monostearate, monolaurin, polysorbate 20, decyl glucoside, polar solvents, and combinations thereof.
[0143] In a preferred embodiment, particles having the above attributes of porosity, silicon to carbon ratio, and carbon type / ratio may be essentially encapsulated with a coating of appropriate thickness. By essentially encapsulated, Applicants mean that the coating reduces the available (effective) surface area of the Si:C particles by at least 50%, preferably at least 80%. In other embodiments, the coating reduces the available (effective) surface area of the Si:C particles by at least about 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, or at least about 90%.
[0144] The coating may be less than about 500 nm thick, or less than about 400 nm thick, or less than about 300 nm thick, or less than about 200 nm thick. In preferred embodiments, the coating may be less than about 600, 580, 560, 540, 520, 500, 480, 460, 440, 420, 400, 380, 360, 340, 320, 300, 280, 260, 240, 220, 200, 180, 160, 140, 120, or 100 nm thick. It will be understood that the coating varies in thickness, and thus the thicknesses quoted are average thicknesses across the various coated Si:C nanoparticles. Larger particles may have thicker coatings due to the smaller relative volume fraction. However, larger particles may result in poor rate performance. It will be understood that particle size and coating thickness may vary and be optimized for different applications. In one embodiment, the coating thickness is about the same as the spacing between the particles in the composite.
[0145] Lithium ions enter the Si:C composite by solid-state diffusion. In one embodiment, additives such as glucose and / or sucrose enable solid-state diffusion of lithium ions into the Si:C composite.
[0146] In a preferred embodiment, the composite utilizes a low-cost form of silicon. In a preferred embodiment, the silicon is in the form of angular nanoparticles produced using a grinding process. In other preferred embodiments, the silicon nanoparticles are milled in water, and the silicon nanoparticles have an oxide formed on the surface. However, in certain embodiments, the silicon nanoparticles can be milled with or without oxidation or partial oxidation. In other embodiments, the silicon nanoparticles are formed by chemical vapor deposition (CVD), which may have varying levels of oxidation or no oxidation. The oxidized or partially oxidized silicon nanoparticles can be treated to remove the oxidation prior to use in the present invention. Current state-of-the-art processes favor silicon with a minimal oxide layer. However, applicants have surprisingly found that good performance can still be achieved using oxidized or partially oxidized silicon nanoparticles. In some embodiments, applicants have surprisingly found that using oxidized or partially oxidized silicon nanoparticles provides high specific capacity for the Si:C composites of the present invention. This is because, traditionally, the presence of oxygen (present as an oxide layer on silicon) is expected to reduce the specific capacity of the Si:C composite.
[0147] In some embodiments, the oxide layer may be modified by the introduction of elements such as lithium and / or magnesium and / or nitrogen. These layers may improve lithium ion diffusion and may also react with the oxide, thereby reducing reactions with the electrolyte during initial charge / discharge, thus aiding first cycle efficiency.
[0148] Applicants have surprisingly found unexpectedly high first cycle efficiencies (low coulombic efficiency loss on the first cycle) using Si:C composites with high silicon content. In some embodiments, lithium ion batteries comprising the Si:C composites described herein have a first cycle efficiency of greater than about 75%. In some embodiments, lithium ion batteries comprising the Si:C composites have a first cycle efficiency of greater than about 80%, greater than about 85%, or greater than about 90%. In some embodiments, lithium ion batteries comprising the Si:C composites have a first cycle efficiency of about 75% to about 95%, about 80% to about 95%, about 80% to about 90%, or about 85% to about 90%. In some embodiments, lithium ion batteries have a first cycle efficiency of 88%.
[0149] Applicants have also surprisingly found that the Si:C composites of the present invention have high specific capacity. In some embodiments, the Si:C composites have a delithiation capacity of greater than about 2500 mAh / g, greater than about 2700 mAh / g, greater than about 2800 mAh / g, greater than about 2900 mAh / g, or greater than about 3000 mAh / g. In some embodiments, the Si:C composites have a delithiation capacity of about 2500 mAh / g to about 3500 mAh / g, about 2700 mAh / g to about 3300 mAh / g, about 2900 mAh / g to about 3200 mAh / g, or about 3000 mAh / g to about 3200 mAh / g. In some embodiments, the Si:C composites have a delithiation capacity of about 3100 mAh / g.
[0150] In the method of the present invention, the dispersion can be spray-dried to form particles with a diameter of about 10 μm. In other embodiments, the dispersion can be spray-dried to form particles with a diameter of about 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, or about 25 μm. This diameter can be varied using known spray drying parameters to achieve desired particle size. As will be understood by those skilled in the art, particle diameter can be adjusted to provide different performance in terms of energy density and power.
[0151] As will be appreciated by one of ordinary skill in the art, any suitable temperature can be used for the heat treatment step of the present invention. In some embodiments, the heat treatment is performed at a temperature greater than about 700°C, greater than about 750°C, greater than about 800°C, greater than about 850°C, or greater than about 950°C. In some embodiments, the heat treatment is performed at a temperature between about 700°C and about 1000°C, between about 750°C and about 950°C, or between about 800°C and about 900°C. In some embodiments, the heat treatment is performed at a temperature of about 850°C.
[0152] The method of the present invention may optionally utilize a step of passivating sites in the cell that are active to the electrolyte. Such sites may reduce first cycle efficiency and cycle life. Examples of such steps include high temperature treatment, introduction of halogen gas during high temperature treatment, and introduction of lithium via evaporation of lithium metal during a pyrolysis step or a chemical vapor deposition (CVD) or atomic layer deposition (ALD) step.
[0153] Example 1 Silicon nanoparticles were produced by grinding silicon particles in a water-based medium using a high-speed ball mill. Carbon nanotubes were dispersed in water using a suitable surfactant, such as a non-ionic surfactant. The silicon nanoparticles / water mixture, the carbon nanotubes / water mixture, and glucose were then dispersed in an aqueous solution using a suitable surfactant. The mixture was then spray dried to obtain particles with an average size of about 18 μm in diameter. The particles were then pyrolyzed in a reducing H2 / Ar atmosphere at about 850° C. After pyrolysis of the surfactant and glucose, the following properties were obtained:
[0154] The silicon to carbon nanotube ratios ranged from about 90:10 to about 96:4. Even though the carbon content was low, very high porosity was maintained (which was unexpected since carbon typically provides the porosity in Si:C composites). We found that a Si:C composite with a Si:C ratio of 92:8 resulted in a porosity of 54%. In this example, single-walled carbon nanotubes (SWCNTs) were used without any other carbon source. Porosity was measured by mercury porosimetry and supported by SEM (Figure 3).
[0155] Figure 1 shows a scanning electron microscope image of the particles. The porous carbon network (1) contains silicon nanoparticles (2) that are well distributed, i.e., most of the nanoparticles are not in contact with each other.
[0156] The carbon coating was deposited on the particles using fluidized bed chemical vapor deposition (CVD) and propane gas at about 1000° C. and a carrier gas ratio of 32% propane to 5% H in argon. Scanning electron microscopy showed that the thickness of the coating ranged from about 200 nm to about 300 nm.
[0157] FIG. 2 shows scanning electron microscope images of a particle before (a) and after (b) coating. It can be seen that the coating seals at least 90% of the surface. In a similar experiment, the coating increased the surface area by approximately 100 m2. 2 / g to about 5m 2 / g, indicating that the particles were effectively encapsulated by the coating.
[0158] Half cells were fabricated using the composite material and a carboxymethyl cellulose (CMC) / styrene-butadiene rubber (SBR) binder with Imerys C45 carbon black as the conductive additive. The ratio of composite to binder to C45 was 8:1:1. Lithium metal was the counter electrode. The composite delivered a capacity of about 3100 mAh / g and a first cycle efficiency of about 88% (96:4 Si:C composite).
[0159] Comparative Example 1 The procedure in Example 1 was used, but no glucose was added and no coating step was performed. The composite delivered only about 240 mAh / g capacity with a first cycle efficiency of about 70%. Applicants hypothesize that without glucose, lithium ions cannot adequately diffuse through the carbon solid, thus reducing capacity.
[0160] Comparative Example 2 The procedure in Example 1 was used, but no coating was applied. The capacity was about 1000 mAh / g. However, the first cycle efficiency was only about 60%, indicating that a coating was necessary to provide a reasonable first cycle efficiency.
[0161] Example 2 - Lithium-ion battery (LIB) Battery electrodes can be formed using the Si:C composite, for example as described in Example 1, to provide a coin cell battery.
[0162] Referring to Figure 4, an example of a lithium ion battery 100 (i.e., lithium ion cell) is shown that includes an anode comprising nanosilicon particles produced by the methods disclosed herein. Figure 4 shows a coin-on-coin lithium ion battery 100 having a first component 112 and a second component 114 that are composed of conductive materials and can function as electrical contacts. However, it should be noted that the battery 100 can be constructed according to any lithium ion battery configuration as is known in the art. Within or attached to the first component 112 is an anode 116 that includes a Si:C composite produced by the methods of the present invention, within or attached to the second component 114 is a cathode 120, and a separator 118 is disposed between the anode 116 and the cathode 120.
[0163] The insulator 122 ensures that the anode 116 is in conductive contact only with the first component 112 and the cathode 120 is in conductive contact only with the second component 114, such that conductive contact with both the first component 112 and the second component 114 closes an electrical circuit and allows electrical current to flow via electrochemical reactions at the anode 116 and cathode 120. Coin-on-coin lithium ion battery configurations, as well as other electrode and component configurations, are well known in the art and the anode of the present invention can be readily configured into any type of lithium ion battery, as will be apparent to one of ordinary skill in the art.
[0164] In an exemplary lithium-ion battery configuration using an electrolyte, various electrolytes may be used. An exemplary non-limiting electrolyte includes 1.15 M LiPF6 in a mixture of ethylene carbonate (EC) / ethyl methyl carbonate (EMC) / ethyl propionate (EP) / fluoroethylene carbonate (FEC) in a weight ratio of 27:35:27:10, with additives such as propylene sulfate (PS) and adiponitrile (AND).
[0165] The coin cells were characterized and we found a very high specific capacity (96%Si 4%C, Si:C material) as tested with a delithiation capacity of 3,100mAh / g. We also found an unexpectedly high first cycle efficiency of 88% (low coulombic efficiency loss due to the first cycle). This was surprising because the water-based treatment of silicon and SWCNTs with the use of surfactants (including binders with carboxymethylcellulose) did not cause a significant adverse effect on the capacity of the silicon, thereby reducing capacity, as would be expected by the introduction of oxygen on the silicon (by forming an oxide layer on the silicon).
[0166] Although the invention has been described with reference to specific examples, it will be appreciated by those skilled in the art that the invention can be embodied in many other forms.
Claims
1. A silicon composite comprising nanoscale silicon and carbon in a weight ratio (silicon:carbon) of about 75:25 to about 99:1, and having a volume fraction of porosity of about 20 to about 70%.
2. 10. The composite of claim 1, wherein the weight ratio of the nanoscale silicon to carbon is from about 90:10 to about 96:
4.
3. 3. The composite of claim 1 or 2, wherein the volume fraction of porosity is from about 50% to about 60%.
4. 2. The composite of any one of the preceding claims, wherein the porosity of the composite accommodates swelling of up to about 300% during a lithiation-delithiation process.
5. 10. The composite of any one of the preceding claims, wherein the carbon is a fibrous form of carbon, such as carbon nanotubes (CNTs), and / or thin nanoplates, such as graphene or graphene oxide or reduced graphene oxide, or a combination thereof.
6. 10. The composite of any one of the preceding claims, further comprising carbon produced by pyrolysis of polymer precursors such as sugars, including glucose, sucrose, fructose, and the like.
7. 10. A composite according to any one of the preceding claims, sealed with a carbon coating of suitable thickness.
8. 8. The composite of claim 7, wherein the coating reduces the available (effective) surface area of the Si:C particles by about 50 to about 80%.
9. 9. The composite of claim 7 or 8, wherein the coating is less than about 500 nm thick.
10. 13. A composite according to any one of the preceding claims for use as an anode or cathode in a lithium-based battery.
11. An anode or cathode for a lithium-based battery comprising the silicon composite of any one of claims 1 to 9.
12. 12. A half cell for a lithium ion battery comprising the anode or cathode of claim 11, a binder, and a conductive additive in a weight ratio of composite to binder to conductive additive of about 8:1:1, about 9:0.5:0.5, about 95:0.2:0.3, or about 97:1:
2.
13. The half cell of claim 12, wherein the binder is carboxymethyl cellulose (CMC) / styrene-butadiene rubber (SBR) and the conductive additive is Imerys C45 carbon black.
14. 14. The half cell of claim 12 or 13, wherein the counter electrode is lithium metal.
15. 12. A lithium ion battery comprising the anode of claim 11, a cathode, an electrolyte, and a separator.
16. A method for making a silicon composite comprising nanoscale silicon and carbon according to any one of claims 1 to 10, comprising: (a) preparing a dispersion of silicon nanoparticles and selected morphology(s) of carbon; (b) spray drying the dispersion to form essentially spherical, micrometer-sized composite particles; (c) heat treating the composite particles to pyrolyze and / or burn off any polymer and strengthen the composite particles; (d) coating the composite particles with carbon to form a Si:C composite; (e) optionally adding additional elements such as lithium, magnesium, nitrogen, and halogen gases to the composite either during the heating step (c) or the coating step (d), or during a subsequent heat treatment step.
17. A method for making a silicon composite comprising nanoscale silicon and carbon according to any one of claims 1 to 10, comprising: (a) preparing a dispersion of silicon nanoparticles by grinding in water and maintaining a mixture of silicon and water; (b) optionally preparing a separate dispersion of the selected form(s) of carbon in water, optionally including one or more surfactants; (c) adding the carbon dispersion and optional surfactant mixture (or carbon in undispersed form) to the silicon-water dispersion; (d) dispersing the resulting mixture; (e) spray drying the resulting dispersed Si:C mixture to form essentially spherical particles; (f) heat treating the essentially spherical particles to pyrolyze and / or burn off any polymer and strengthen the spherical Si:C particles; (g) coating the heat-treated spherical Si:C particles with carbon using a chemical vapor deposition process to form a carbon-coated Si:C composite; (h) optionally adding additional elements to the composite, such as lithium, magnesium, nitrogen, and halogen gases, either during mixing step (c) or dispersing step (d), or during a subsequent heat treatment, to add additional elements to the carbon coated Si:C composite.
18. 18. The method of claim 16 or 17, wherein the selected form(s) of carbon comprises carbon nanotubes (CNTs) and / or thin nanoplates, such as graphene or graphene oxide or reduced graphene oxide, and combinations thereof.
19. The method of any one of claims 16 to 18, wherein the weight ratio of the nanoscale silicon to carbon is from about 90:10 to about 96:
4.
20. The method of any one of claims 16 to 19, wherein the surfactant(s) is acidic.
21. 21. The method of any one of claims 16 to 20, wherein the carbon further comprises carbon produced by pyrolysis of polymer precursors such as sugars, including glucose, sucrose, fructose, and the like.
22. The method of any one of claims 16 to 21, wherein the volume fraction of porosity is from about 50% to about 60%.
23. A method according to any one of claims 16 to 22, wherein the composite is sealed with a carbon coating of suitable thickness.
24. The method of claim 23, wherein the coating reduces the available (effective) surface area of the Si:C particles by about 50 to about 80%.
25. 25. The method of claim 23 or 24, wherein the coating is less than about 500 nm thick.
26. A silicon composite comprising nanoscale silicon and carbon when produced by the process of any one of claims 16 and 18-25.
27. A carbon coated silicon composite comprising nanoscale silicon and carbon when produced by the method of any one of claims 17 to 25.
28. 28. An anode for a lithium ion battery comprising the silicon composite of claim 26 or the carbon coated silicon composite of claim 27.
29. 30. A half cell for a lithium ion battery comprising the anode of claim 28, a binder, and a conductive additive in a weight ratio of composite to binder to conductive additive of about 8:1:
1.
30. 30. A lithium ion battery comprising the anode of claim 28, a cathode, an electrolyte, and a separator.
31. A silicon composite particle comprising at least 75% silicon relative to carbon and at least 50% pores, said carbon being composed of carbon nanotubes.
32. A silicon composite material comprising at least 50% pores and the amount of silicon in the material is greater than 90%.